A Survey of Preservation and Conservation of Information Resources in Private University Libraries, South-west, Nigeria - Bashorun, Musediq Tunji; Idogun-Omogbai, Esther Kehinde; Muhammad, Jamiu Oladele (Record and Library Journal, 2021)
Background of study: Preservation and conservation of the cultural, social and technical context of our heritage are germane. Purpose: The study examined the preservation and conservation of information resources in selected private university libraries in South-west Nigeria. Eight (8) selected private universities in South-west, Nigeria with the population consisted of one hundred thirty-seven respondents which comprised of library professionals and para-professionals. Method: The study employed a survey research design and random sampling technique. Data collected with aids of semi- structured questionnaire and was analysed using frequency, mean and standard deviation with the aid of a Statistical Package for Social Sciences (IBM-SPSS) version 20.0 Results: The findings revealed that book becoming torn is the highest nature of deterioration followed by vandalisation, mutilation and brittle of print library materials. Moreover, the study revealed that digital preservation level of utilisation is low and is not extensively used in selected private university libraries. Conclusion: The study concluded that preservation and conservation techniques are recognized in the selected university libraries, but the digital preservation techniques are not adequately used due to various constraints. One of the recommendations made was the provision of formal training for library staff on preservation and conservation of information resources.